Sector Inquiry into Cross-Border E-Commerce: Challenges and Practical Implications for European Union Completion Law - Szmigielski, Artur (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The aim of this article is to show what the practical implications are regarding the Commission inquiry into e-commerce sector launched on 6 May 2015. Because of their specific and dynamic nature, the application of competition law to online markets may prove challenging. Therefore, the focus will be also directed to challenges that could be faced when anti-competitive practices in e-commerce sector are strictly enforced. The question is whether traditional competition analysis may be sufficiently able to reflect the way in which competition takes place on digital markets.